Gargalos e demandas da infraestrutura ferroviária e os investimentos do PAC: Mapeamento IPEA de obras ferroviárias - Carlos Alvares da Silva Campos Neto; Bolívar Pêgo Filho; Alfredo Eric Romminger; Ians\~a Melo Ferreira; Leonardo Fernandes Soares Vasconcelos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The present work discusses the main economical and institutional problems that involve the Brazilian railway system. Firstly, we characterize the segment, presenting the main concepts and a short overview of Brazilian railways, it's history and managing institutions. Next, we present a short analysis of the main laws which regulate the sector, along with a discussion about the economic aspects of the concession contracts celebrated upon the rail structure. Then, we describe the financing model for this segment as well as the investments it's received-public as well as private-for expanding and operating. Afterwards, we present the major infra-structural demands, consolidating the Mapeamento Ipea de Obras Ferroviárias, followed by an analysis of how has the government program, Programa de Aceleraç\~ao do Crescimento (PAC), been impacting over those needs. And finally, we describe the general results of our analysis.
Keywords: L92; H42; H45; G18; 330; Schienenverkehr; Brasilien